2009
DOI: 10.1051/0004-6361/200912375
|View full text |Cite
|
Sign up to set email alerts
|

Global and local expansion of magnetic clouds in the inner heliosphere

Abstract: Context. Observations of magnetic clouds (MCs) are consistent with the presence of flux ropes detected in the solar wind (SW) a few days after their expulsion from the Sun as coronal mass ejections (CMEs). Aims. Both the in situ observations of plasma velocity profiles and the increase of their size with solar distance show that MCs are typically expanding structures. The aim of this work is to derive the expansion properties of MCs in the inner heliosphere from 0.3 to 1 AU. Methods. We analyze MCs observed by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
219
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(285 citation statements)
references
References 37 publications
61
219
5
Order By: Relevance
“…Calculations of the average magnetic field strength over the duration of each cloud reveal that it is comparable (∼17 nT) in all but one of these events (∼32 nT), and the values obtained are within the range expected for a typical magnetic cloud [Lepping et al, 2003]. We find that z is smaller than the mean value obtained for the nonperturbed (not overtaken) magnetic clouds analyzed by Démoulin et al [2008] at 1 AU (z = 0.8 ± 0.2), and those analyzed by Gulisano et al [2010] between 0.3 and 1 AU (z = 0.9 ± 0.2). This is consistent with the presence of an overtaking solar wind stream behind these magnetic clouds, as the lowest values of z are found for overtaken clouds (see Table 1).…”
Section: Prevalence Of Substructure Within Magnetic Cloudssupporting
confidence: 70%
See 2 more Smart Citations
“…Calculations of the average magnetic field strength over the duration of each cloud reveal that it is comparable (∼17 nT) in all but one of these events (∼32 nT), and the values obtained are within the range expected for a typical magnetic cloud [Lepping et al, 2003]. We find that z is smaller than the mean value obtained for the nonperturbed (not overtaken) magnetic clouds analyzed by Démoulin et al [2008] at 1 AU (z = 0.8 ± 0.2), and those analyzed by Gulisano et al [2010] between 0.3 and 1 AU (z = 0.9 ± 0.2). This is consistent with the presence of an overtaking solar wind stream behind these magnetic clouds, as the lowest values of z are found for overtaken clouds (see Table 1).…”
Section: Prevalence Of Substructure Within Magnetic Cloudssupporting
confidence: 70%
“…Nearly all of the clouds in this study are followed by fast solar wind streams. We have found that the nondimensional expansion rates of these MCs are low, with values of z < 0.8, indicating that these magnetic clouds are perturbed [Gulisano et al, 2010]. As a fast stream overtakes a magnetic cloud, it is expected to compress the flux rope and so decrease its expansion rate, as shown in MHD simulations [Xiong et al, 2006] and in in situ observations [Gulisano et al, 2010].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…4 panel 3) smoothly and monotonically increases beyond this time, with a strong discontinuity of B y a bit later, on March 26, 13:00 UT. At the center of the flux rope we expect a global extreme of F y (Dasso et al 2006Gulisano et al 2010), in particular, as it was observed when this same cloud was located at 1 AU (panel 3 of Fig. 3).…”
Section: Acceleration and Expansionsupporting
confidence: 59%
“…However, observations of the MC field configuration are approximately consistent with this magnetic configuration at different heliodistances, ranging from 0.3 to 5 AU (e.g., Bothmer & Schwenn 1998;Leitner et al 2007), so that we expect a small anisotropy on the expansion along different cloud directions (i.e., l ≈ m ≈ n). From observations of different MCs at significantly different heliodistances (Wang et al 2005b;Leitner et al 2007) and from observations of the velocity profile slope from single satellite observations (Démoulin et al 2008;Gulisano et al 2010), it has been found that ζ ≈ 0.8. Since ζ is a combination of l and n, which depends on γ for each cloud, a systematic difference on l and n would be detected in a set of MCs with variable γ angle.…”
Section: Magnetic Fieldmentioning
confidence: 99%